Comparative Analysis of Adverse Drug Reactions Associated with Fluoroquinolones and Other Antibiotics: A Retrospective Pharmacovigilance Study - Alshareef H; Alenzi KA; Albalawi BR; Alanazi RM; Albalawi NS; Alasoufi WS; Alqifari S; Ahmed R; Ali MAS (Drug, Healthcare and Patient Safety)
Hanan Alshareef,1 Khalidah A Alenzi,2 Budor R Albalawi,3 Rinas M Alanazi,3 Nawal S Albalawi,3 Wedad Saleem Alasoufi,3 Saleh Alqifari,1 Rehab Ahmed,4 Mostafa AS Ali1 1Pharmacy Practice Department, Faculty of Pharmacy, University of Tabuk, Tabuk, Saudi Arabia; 2Transformation and Business Development, Tabuk Health Cluster, Tabuk, Saudi Arabia; 3Faculty of Pharmacy, University of Tabuk, Tabuk, Saudi Arabia; 4Division of Microbiology, Immunology and Biotechnology, Department of Natural Products and Alternative Medicine, Faculty of Pharmacy, University of Tabuk, Tabuk, Saudi ArabiaCorrespondence: Hanan Alshareef, Pharmacy Practice Department, Faculty of Pharmacy, University of Tabuk, Tabuk, Saudi Arabia, Email halsharef@ut.edu.saBackground: Fluoroquinolones (FQs) are among the most popular antimicrobials that are highly effective against various infections. Although FQs are the most frequently used and generally tolerated, there are issues with their safety. This study assessed the rate, severity, seriousness, outcomes, and types of FQs adverse drug reactions (ADRs) in reports submitted to a regional spontaneous ADR database.Methods: This was a retrospective cross-sectional observational study involving all patients with reported ADRs related to FQs or other antibiotics (ABs) that were submitted to the Regional Pharmacovigilance Center (PVC) database between January 2019 and December 2022. Data were extracted in the form of Saudi ADR from the PVC database, which is consistent with the MedWatch ADR form of the U.S Food and Drug Authority (FDA).Results: In total, 605 ADRs related to antibiotic use were reported. ADRs caused by FQs use were the most frequently reported (177; 29.3%), followed by penicillin (100; 23.4%) and cephalosporin (90; 21%). There was no significant difference in ADRs caused by FQs between men (104; 58%) and women (OR 1.17, 95% CI 0.82– 1.67, p=0.386). FQ-related ADRs were more frequent among those over 40 years-old (OR 1.56, 95% CI 1.09– 2.22, p=0.015). Most of the detected FQ-related ADRs were of moderate severity (157; 88.7%), required interventions (83; 46.9%), and recovered after receiving medical interventions (154; 87%). Patients who received FQs were fourfold more likely to experience neurological adverse events (OR 4.15, 95% CI 2.48– 6.93, p < 0.001).Conclusion: The FQs drug class exhibited a higher incidence of ADRs than other ABs. Regularly assessing the safety of ABs is crucial to improve public and healthcare providers’ awareness of the correct utilization of ABs and to limit the use of FQs to infections that cannot be effectively managed with alternative ABs.Keywords: adverse drug reactions (ADRs), fluoroquinolones (FQs), antibiotics (ABs), pharmacovigilance